Dysfunctional Family in Tabitha Suzuma’s Forbidden - Rani Anggi Adikasih; Anik Cahyaning Rahayu (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study examines the portrayal of dysfunctional family in Tabitha Suzuma's Forbidden. Itaims to identify the signs of dysfunctional family, analyze the causes of family dysfunction, and examineits psychological impacts on the main characters, Lochan and Maya. This study employs a qualitativedescriptive research design using a psychological approach to literature. The data source is the novelForbidden (2010) by Tabitha Suzuma, and the analysis is conducted using Murray Bowen's FamilySystems Theory and Psychoanalytic Literary Criticism. The findings reveal that the Whitely familyexhibits several signs of dysfunctional family, including low differentiation of self, triangulation,emotional cutoff, parentification (role reversal), and misplaced emotional attachment. The study alsofinds that parental neglect and absence, emotional instability, poor communication, and lack ofemotional support contribute to family dysfunction. These conditions result in anxiety, emotionaldistress, low self-esteem, unhealthy emotional dependency, and social isolation experienced by Lochanand Maya. The findings suggest that dysfunctional family environments profoundly shape emotionaldevelopment, psychological well-being, and interpersonal relationships, leading to emotionaldependency and blurred family boundaries.